Northward geographic diversification of a kleptoparasitic spider Argyrodes lanyuensis (Araneae, Theridiidae) from the Philippine Archipelago to Orchid Island. Issue 16 (22nd July 2021) - Responte, Mae; Chiu, Yi‐Fan; Peng, Po; Brown, Rafe M.; Dai, Chia‐Yen; Su, Yong‐Chao
Abstract: Oceanic islands are unique geographic systems that promote local adaptations and allopatric speciation in many of their highly endemic taxa. This is a common case in the Philippine Archipelago, where numerous unrelated taxa on islands have been inferred to have diversified in isolation. However, few cases have been reported in invertebrates especially among parasitic organisms. Here, we tested for biogeographical structure in novel populations of the "generalist" kleptoparasitic spider, Argyrodes lanyuensis Yoshida, Tso & Severinghaus, 1998 in the Philippines. Results showed that, in addition to Orchid/Lanyu Island, this species has a wide geographic distribution in the Philippine Archipelago. The estimated divergence time of this lineage using the mitochondrial cytochrome oxidase 1 (mt‐CO1) suggests that this species diverged ca 3.12 MYA, during the Pliocene. Two reciprocal monophyletic clades were elucidated in A. lanyuensis, but with limited differentiation across Pleistocene Aggregate Island Complex (PAIC) boundaries and modern‐day islands. However, in our analyses of morphological variation, we identified two phenotypically differentiated units in males (Orchid Island, Taiwan + Luzon, Philippine PAIC populations vs. Palawan + West Visayan + Mindanao PAIC populations). We infer that this species diverged in the southern portion of the Philippine Archipelago and only recently colonized Orchid Island. Our study provides new information on the extensive distribution of A. lanyuensis outside Orchid Island, Taiwan, but we documented a very limited geographically associated genetic variation. Our study points to behavioral phenomena such as foraging behavior as essential contributor to the evolutionary process of species diversification, in contrast to the traditionally invoked geographic drivers of divergence. Abstract : The kleptoparasitic spider, Argyrodes lanyuensis Yoshida, Tso & Severinghaus, 1998, has been considered endemic in Orchid/Lanyu Island, Taiwan, since it was first described. However, our study revealed novel populations of A. lanyuensis on at least six islands of the Philippine archipelago. We inferred the diversification and colonization patterns of this species and assessed whether a strongly subdivided geographic system was effective in generating a pronounced geographically structured variations among its populations. It was revealed that this species diverged from the southern portion of the Philippine Archipelago and only recently colonized Orchid Island.